Acute Encephalopathy Is Associated With Worse Outcomes In COVID-19 Patients (2020)
Background Acute encephalopathy with COVID-19 has been reported in several studies but its impact on outcomes remains unclear. We hypothesized that hospitalized COVID-19 patients with encephalopathy have worse COVID-19 related outcomes. Methods We used TriNetX, with a large COVID-19 database, collecting real-time electronic medical records data. We included hospitalized COVID-19 patients since January 20, 2020 who had encephalopathy based on ICD-10 coding. We examined clinical outcomes comprising need for critical care services, intubation and mortality among these patients and compared it with patients without encephalopathy before and after propensity-score matching. Results Of 12,601 hospitalized COVID-19 patients, 1092 (8.7%) developed acute encephalopathy. Patients in the acute encephalopathy group were older (67 vs. 61 years) and had higher prevalence of medical co-morbidities including obesity, hypertension, diabetes, heart disease, COPD, chronic kidney and liver disease among others. Before and after propensity score-matching for co-morbidities, patients with acute encephalopathy were more likely to need critical care services (35.6% vs. 16.9%, p < 0.0001), intubation (19.5% vs. 6.0%, p<0.0001) and had higher 30-day mortality (24.3% vs. 17.9%, p 0.0002). Conclusion Among hospitalized COVID-19 patients, acute encephalopathy is common and more likely to occur in patients with medical co-morbidities and are more likely to need critical care, intubation and have higher 30-day mortality even after adjusting for age and underlying medical co-morbidities.